The complete Jacobian becomes (make sure you get this!) $$ \begin{align*} J_{i,i} &= \frac{\partial F_i}{\partial u_i} = \frac{\partial A_{i,i-1}}{\partial u_i}u_{i-1} + \frac{\partial A_{i,i}}{\partial u_i}u_i + A_{i,i} + \frac{\partial A_{i,i+1}}{\partial u_i}u_{i+1} - \frac{\partial b_i}{\partial u_{i}}\\ &= \frac{1}{2\Delta x^2}( -\dfc^{\prime}(u_i)u_{i-1} +2\dfc^{\prime}(u_i)u_{i} -\dfc(u_{i-1}) + 2\dfc(u_i) - \dfc(u_{i+1})) +\\ &\quad a -\frac{1}{2\Delta x^2}\dfc^{\prime}(u_{i})u_{i+1} - b^{\prime}(u_i)\\ J_{i,i-1} &= \frac{\partial F_i}{\partial u_{i-1}} = \frac{\partial A_{i,i-1}}{\partial u_{i-1}}u_{i-1} + A_{i-1,i} + \frac{\partial A_{i,i}}{\partial u_{i-1}}u_i - \frac{\partial b_i}{\partial u_{i-1}}\\ &= \frac{1}{2\Delta x^2}( -\dfc^{\prime}(u_{i-1})u_{i-1} - (\dfc(u_{i-1}) + \dfc(u_i)) + \dfc^{\prime}(u_{i-1})u_i)\\ J_{i,i+1} &= \frac{\partial A_{i,i+1}}{\partial u_{i-1}}u_{i+1} + A_{i+1,i} + \frac{\partial A_{i,i}}{\partial u_{i+1}}u_i - \frac{\partial b_i}{\partial u_{i+1}}\\ &=\frac{1}{2\Delta x^2}( -\dfc^{\prime}(u_{i+1})u_{i+1} - (\dfc(u_{i}) + \dfc(u_{i+1})) + \dfc^{\prime}(u_{i+1})u_i) \end{align*} $$